Experimental and numerical heat transfer study of turbulent tube flow through discrete V-winglets - Promvonge, Pongjet; Promthaisong, Pitak; Skullong, Sompol (My University, 2020)
The article presents an experimental and numerical investigation on heat transfer augmentation in a tubular heat exchanger inserted with discrete-V-winglet (DW) tape. Air entered the DW-inserted tube having a uniform wall heat flux in a turbulent flow regime, Reynolds number from 4200 to 25,800. Two arrangements of DWs: V-tip pointing upstream (V-up) and downstream (V-down) were introduced with three relative winglet heights (RB=b/D = 0.1, 0.15 and 0.2) and four relative winglet-pitches (RP=P/D = 0.5, 1.0, 1.5 and 2.0), all at a single angle of attack, α = 30°. Effects of those parameters on the heat transfer/Nusselt number (Nu) and friction factor (f) were examined. Also, a novel thermal-performance enhancement factor (TEF) was put forward. The experimental result has shown that at a given RB, the smallest pitch length (RP=0.5) yields the highest f and Nu. The DW with RB=0.2 and RP=0.5 has the maximum Nu and f of about 3.8 times and 18.8 times, respectively whereas the one with RB=0.15 and RP=1.0 gives the highest TEF of about 1.99 and 2.02 for the V-up and V-down, respectively. Moreover, the DW provides higher TEF than the typical V-winglet as expected. To explore the mechanism of heat transfer, a numerical model of the inserted-tube flow was carried out and the numerical result was validated and found in favorable agreement with available measurement. Flow structures and heat transfer patterns from the simulation such as temperature contours and streamlines including the Nusselt number contours were also proposed.
Keywords: Discrete winglet; Heat exchanger; Thermal performance; Turbulent flow; Vortex generator